Implementasi Metode Promethee II untuk Menentukan Pemenang Tender Proyek (Studi Kasus: Dinas Perhubungan dan LLAJ Provinsi Jawa Timur) - Muhammad Wafi; Rizal Setya Perdana; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Implementation of duties by the Department of Transportation and LLAJ is done by disseminating information about project execution through Layanan Pengadaan Secara Elektronik (LPSE). The large number of bidders requires the Department of Transportation and LLAJ to make a good selection of winners. The winner's assessment can be done by applying the Preference Ranking Method Method of Organizational Methods for Enrichment Evaluation (PROMETHEE II) on the system to consider several alternatives and choose the best alternative based on administrative aspects, quality, price and qualification. The method of Promethee II performs calculations with several stages: weighting, multicriteria preference index calculation for 3 types of preferences, usual, level and quasi then continue by calculating of leaving flow, entering flow, and netflow. Based on the test, the highest accuracy of the system is 84.21% with usual criterion and quasi criterion type preferences. The lowest accuracy is 63.15% with level criterion type preference. The degree of accuracy in testing is influenced by the weighting conditions used for each of the criteria and the type of preferences used in the calculation process. Implementation of Promethee II method is expected to determine the winning bidder with a good assessment process by considering all criteria.